Determination of damping ratios for soils using bender element tests. Issue 111 (August 2018) - Cheng, Z.; Leong, E.C.
Abstract: The use of bender elements to measure small-strain soil properties in the laboratory has become increasingly accessible in recent years. Coupled with the fact that bender elements can be incorporated into conventional test apparatuses such as the triaxial test brings about great savings in time and resources as the bender element tests can be conducted concurrently with conventional geotechnical test for the same soil specimen. While primary (P) and shear (S) waves in bender element tests can provide soil stiffnesses reliably, damping ratio of the soil was seldom determined. This paper attempts to show numerically and experimentally that it is possible to determine the damping ratio of soils by applying the Hilbert transform method (HTM) to the bender element test results. Highlights: Bender element tests are becoming increasingly accessible in laboratory tests. Bender element tests are commonly used to determine stiffness and not damping ratio. Determining damping ratio from bender element test is demonstrated numerically. Method was verified by testing a standard sand and comparing with the literature.